2022
DOI: 10.1016/j.cocis.2021.101557
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of capillary suspensions at diverse length scales: From single capillary bridges to bulk

Abstract: Liquid-liquid-solid systems are becoming increasingly common in everyday life with many possible applications. Here, we focus on a special case of such liquid-liquid-solid systems, namely, capillary suspensions. These capillary suspensions originate from particles that form a network based on capillary forces and are typically composed of solids in a bulk liquid with an added secondary liquid. The structure of particle networks based on capillary bridges possesses unique properties compared with networks forme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 90 publications
(125 reference statements)
0
17
0
1
Order By: Relevance
“…The exact significance of the various measured contact angles and their hysteresis for the actual magnitude of the interparticle capillary force mediated by a liquid bridge have not been clearly understood yet. [55][56][57] However, it has been suggested that a decrease in surface wettability (e.g., an increase in the three-phase contact angle θ) of the liquid bridge would in general cause a decrease in the capillary force (F c ), given F c = f(V bridge )2πrγcosθ, where f(V bridge ) is a function of the liquid bridge volume (not known in closed form) and r is the particle radius. [41,56] It was thus anticipated that in AOT-doped oil, the capillary force mediated by the aqueous bridge between EGaIn droplets would be qualitatively lower than in pristine oil, which explains the formation of the putty-like suspension shown in Figure 1d, where no immediate agglomeration was observed but the suspension was "nicely" thickened in terms of its rheological processability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exact significance of the various measured contact angles and their hysteresis for the actual magnitude of the interparticle capillary force mediated by a liquid bridge have not been clearly understood yet. [55][56][57] However, it has been suggested that a decrease in surface wettability (e.g., an increase in the three-phase contact angle θ) of the liquid bridge would in general cause a decrease in the capillary force (F c ), given F c = f(V bridge )2πrγcosθ, where f(V bridge ) is a function of the liquid bridge volume (not known in closed form) and r is the particle radius. [41,56] It was thus anticipated that in AOT-doped oil, the capillary force mediated by the aqueous bridge between EGaIn droplets would be qualitatively lower than in pristine oil, which explains the formation of the putty-like suspension shown in Figure 1d, where no immediate agglomeration was observed but the suspension was "nicely" thickened in terms of its rheological processability.…”
Section: Resultsmentioning
confidence: 99%
“…[28,[30][31][32][33][34][35][36][37] To further increase the strength of the EGaIn-in-oil suspension, we employed a polymeric liquid bridge, polyethylene glycol diacrylate (PEGDA) with a number average molar mass (M n ) of 250 Da. PEGDA is in the liquid state at room temperature and has a much higher viscosity (15 cP) than water (1 cP); thus, we anticipated that it would form a stronger capillary bridge [55,58,59] between the EGaIn particles. The primary objective of employing a high-viscosity liquid bridge is to enhance the viscous force contribution, rather than the capillary force contribution, to the total rupture force of the liquid bridge.…”
Section: Resultsmentioning
confidence: 99%
“…Increasing the liquid volume further decreases the strength due to particle aggregation. [21,24,25] Particle roughness has several key implications for capillary suspensions: it will affect the shape, strength and number of the liquid bridges, as well as the frictional particle contacts themselves. The formation and strength of liquid menisci between two rough particles has been studied in wet granular media.…”
Section: Introductionmentioning
confidence: 99%
“…These explicit bonds between particles make the capillary suspension networks very different from other attractive particle networks, for example originating from depletion interactions, and result in rigid body movement of the particle flocs. [24] The rupture dynamics experiments of Zanini et al showed that a pinned contact line reduces the rupture force and rupture distance when stretching the liquid meniscus between a rough particle and a liquid-liquid interface compared to a sliding contact line when using a smooth particle. [37] However, pinned contact lines and an increased hysteresis may also increase the rigid body movement in these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Capillary bridges, resulting from the surface tension of fluids, play critical roles in various multiscale adhesion phenomena in nature. Given its strong rearrangement and compaction effect, capillary bridges have been exploited for patterning of nanoarrays, , sintering of ceramic particles, , gelation of suspension, , graphene transfer, stabilization of emulsions, and so forth. In this work, the bubbling involved in the chemical expansion process not only expands the flake graphite to exfoliated graphite worms but also induces abundant capillary bridges that cause these exfoliated graphite worms to jam at the microscale.…”
Section: Introductionmentioning
confidence: 99%